Biological Control Success of a Pasture Pest: Has Its Parasitoid Lost Its Functional Mojo? - Tomasetto, Federico; Casanovas, Paula; Brandt, Samuel N.; Goldson, Stephen L. (Frontiers in Ecology and Evolution, 2018)
Sustainable and integrated pest management often involves insect parasitoids. However, the effectiveness of parasitoids biocontrol has often failed, frequently for obscure reasons. A parasitoid’s success is partly due to its behavioral response to pest density, i.e. its consumer functional response. For many years in New Zealand, a braconid parasitoid, Microctonus hyperodae successfully suppressed a severe ryegrass weevil pest, Listronotus bonariensis. However, there is now evidence that this has severely declined, but that the extent of decline can depend on the pasture species. Here, we tested whether the current functional responses of M. hyperodae to L. bonarensis in two of the most common New Zealand pasture grasses (Lolium multiflorum and L. perenne) reflect observed differences in field parasitism and whether this functional response has changed over time. Our analysis involved data both from 1993 and 2018. We found a type I functional response in L. multiflorum in both years, but the slope of the relationship declined over time. There was no evidence for any type of functional response in L. perenne. This lack of response in the L. perenne coincided with consistently found lower parasitism rates on this host plant than in L. multiflorum; both in the field and laboratory. Here, we found that apparently declining searching efficiency was correlated with the decline in parasitism. This observation supports the hypothesis that parasitism decline could be the result of evolution of resistance based on enhanced evasive behaviour by L. bonariensis.